Efficacy and Safety of Tirzepatide in the Treatment of Obesity: A Review of Current Clinical Trials - Kijowski, Wojciech; Fahim, Knieszko; Franaszek, Jakub; Herchi, Nadia; Jabrzyk, Martyna; Jarczyńska, Patrycja; Klusek, Mateusz; Michalak, Karolina; Przybył, Maciej (Quality in Sport, 2026)
Background: Obesity is a chronic disease with increasing prevalence and substantial health consequences. In recent years, advances in incretin-based pharmacotherapy have enabled greater weight loss than was achievable with earlier medications. Aim: To evaluate the efficacy and safety of tirzepatide in the treatment of obesity based on current clinical trial evidence. Materials and methods: A narrative review of key randomized trials from the SURMOUNT program (including SURMOUNT-1 and SURMOUNT-4), longer-term follow-up data, and meta-analyses was performed. Outcomes included mean percent weight change, clinically relevant weight-loss thresholds, durability of effect after treatment withdrawal, and adverse events. Results: In SURMOUNT-1, tirzepatide produced a significant, dose-dependent reduction in body weight, achieving a mean weight loss of up to approximately 21% at 72 weeks compared with placebo, and a substantial proportion of participants reached ≥20% weight loss at higher doses. In SURMOUNT-4, continued therapy was essential to maintain weight loss, whereas treatment discontinuation was associated with clinically meaningful weight regain. The most common adverse events were gastrointestinal (nausea, diarrhea, vomiting), typically mild to moderate in severity. Conclusions: Tirzepatide is an effective pharmacological option for obesity with an acceptable safety profile; however, maintenance of benefits requires long-term treatment. Further studies are needed to clarify durability of effect and long-term safety over multiple years.